Pengaruh Social Media Marketing dan Fomo terhadap Purchase Intention Produk Cicil Emas pada PT Pegadaian Pontianak dengan Brand Trust sebagai variabel Moderasi - Gavin Satria Pangestu; Wendy Wendy; Harry Setiawan; Nur Afifah; Bintoro Bagus Purmono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of digital technology has driven changes in financial services marketing strategies, including for PT Pegadaian's Gold Installment product, which faces competition from digital investment platforms. This situation has prompted Pegadaian to optimize social media marketing and leverage the Fear of Missing Out to increase purchase intention, particularly among the younger generation. This study aims to analyze the influence of social media marketing and Fear of Missing Out on purchase intention for the Gold Installment product, with brand trust as a moderating variable. The study used a quantitative approach with explanatory research through online questionnaire data collection from respondents who met the research criteria. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling method with WarpPLS 8.0. The results show that social media marketing and Fear of Missing Out have a positive and significant effect on purchase intention. Furthermore, brand trust has been shown to strengthen the influence of both variables on purchase intention. This research is expected to provide theoretical contributions to the development of consumer behavior studies and practical implications for PT Pegadaian in strengthening its digital marketing strategy and increasing purchase interest in the Gold Installment product.